SN 2018gj: A Short Plateau Type II Supernova with Persistent Blueshifted Ha Emission - Rishabh Singh Teja; Avinash Singh; D. K. Sahu; G. C. Anupama; Brajesh Kumar; Tatsuya Nakaoka; Koji S Kawabata; Masayuki Yamanaka; Ali Takey; Miho Kawabata (The Astrophysical Journal, 2023)
We present an extensive, panchromatic photometric (UV, optical, and near-IR) and low-resolution optical spectroscopic coverage of a Type IIP supernova SN 2018gj that occurred on the outskirts of the host galaxy NGC 6217. From the V- band light curve, we estimate the plateau length to be ∼ 70 ± 2 days, placing it among the very few well-sampled short plateau supernovae (SNe). With V -band peak absolute magnitude M _V ≤ −17.0 ± 0.1 mag, it falls in the middle of the luminosity distribution of the Type II SNe. The color evolution is typical to other Type II SNe except for an early elbow-like feature in the evolution of V − R color owing to its early transition from the plateau to the nebular phase. Using the expanding photospheric method, we present an independent estimate of the distance to SN 2018gj. We report the spectral evolution to be typical of a Type II SNe. However, we see a persistent blueshift in emission lines until the late nebular phase, not ordinarily observed in Type II SNe. The amount of radioactive nickel ( ^56 Ni) yield in the explosion was estimated to be 0.026 ± 0.007 M _⊙ . We infer from semianalytical modeling, nebular spectrum, and 1D hydrodynamical modeling that the probable progenitor was a red supergiant with a zero-age-main-sequence mass ≤13 M _⊙ . In the simulated hydrodynamical model light curves, reproducing the early optical bolometric light curve required an additional radiation source, which could be the interaction with the proximal circumstellar matter.